Use of new natural dyes extracted from different sections of Salvia urica in dye-sensitized solar cells - Aslan, Fehmi; Yamaç, Halil İbrahim (My University, 2024)
In this study, natural dyes that were obtained from the branches, flowers and leaves of Salvia urica were utilized as sensitizers in TiO2-based dye-sensitized solar cells (DSSCs). XRD and FE-SEM were used to analyze the crystal structure and morphological properties of the produced TiO2 nanopowders, respectively. The optical properties of natural dyes extracted from the Salvia urica plant were investigated by UV-vis spectroscopy. Functional groups in natural dyes were detected by FTIR spectroscopy, while DSSCs were evaluated for photovoltaic performance and electrochemical impedance. The findings show that the flower dye absorbs a wider wavelength of light in the visible region and the interaction between the carbonyl/hydroxyl groups and the TiO2 surface is very strong, which is why it is the most efficient way of power conversion among all other natural sensitizers. The efficiencies of DSSCs sensitized with flower, branch and leaf dye of Salvia urica were 0.33%, 0.28%, and 0.19%, respectively.
Keywords: Photovoltaic performance; Natural dyes; Dye-sensitized solar cells